2022
DOI: 10.3390/pharmaceutics14010113
|View full text |Cite
|
Sign up to set email alerts
|

Elovanoids Counteract Inflammatory Signaling, Autophagy, Endoplasmic Reticulum Stress, and Senescence Gene Programming in Human Nasal Epithelial Cells Exposed to Allergens

Abstract: To contribute to further understanding the cellular and molecular complexities of inflammatory-immune responses in allergic disorders, we have tested the pro-homeostatic elovanoids (ELV) in human nasal epithelial cells (HNEpC) in culture challenged by several allergens. ELV are novel bioactive lipid mediators synthesized from the omega-3 very-long-chain polyunsaturated fatty acids (VLC-PUFA,n-3). We ask if: (a) several critical signaling events that sustain the integrity of the human nasal epithelium and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…In addition, some epithelial cells previously thought not to produce cytokines [54], such as epithelial cells in the respiratory tract, epidermis, and digestive tract, have also been reported to release IL-1β in allergic diseases [55,56]. It was also found that nasal mucosal epithelial cells produced IL-1β after being stimulated by allergens [57], which was consistent with the findings in in vitro human nasal mucosa epithelial cell models exposed to allergen or in in vivo AR animal models [58,59]. Therefore, how to precisely regulate IL-1β in the AR nasal mucosal epithelium has become a hot research topic.…”
Section: Relationships Of Il-1β With Different Cells In Allergic Dise...supporting
confidence: 86%
“…In addition, some epithelial cells previously thought not to produce cytokines [54], such as epithelial cells in the respiratory tract, epidermis, and digestive tract, have also been reported to release IL-1β in allergic diseases [55,56]. It was also found that nasal mucosal epithelial cells produced IL-1β after being stimulated by allergens [57], which was consistent with the findings in in vitro human nasal mucosa epithelial cell models exposed to allergen or in in vivo AR animal models [58,59]. Therefore, how to precisely regulate IL-1β in the AR nasal mucosal epithelium has become a hot research topic.…”
Section: Relationships Of Il-1β With Different Cells In Allergic Dise...supporting
confidence: 86%
“…It has shown that in administering HDMs OIT, the oral route does not seem to offer a superior efficacy over the conventional routes; this conflict may be attributed to patient selection and allergen bioavailability to the gut due to gastric enzymatic degradation ( 9 , 10 ). HDMs are a prevalent indoor allergen causing allergic respiratory diseases, including AR and allergic asthma ( 11 ). The objective of this study is to verify a hypothesis that Dermatophagoides farina ( Df ) encapsulated in enteric-coated capsules might effectively treat HDMs-induced AR through OIT, achieving a similar or superior effect to that of SCIT.…”
Section: Introductionmentioning
confidence: 99%